ANALISIS SIMBOL PADA UPACARA SEDEKAH LAUT DI PANTAI TELUK PENYU CILACAP - Donny Khoirul Azis; Tsuroya Firdausi (STAI Sufyan Tsauri Majenang, 2021)
This study aims to determine the Islamic symbols contained in the ceremony of sea alms and to know the context of Islamic symbols that manifest in the life of the Cilacap sea turtle community. The method used in this study is qualitative by collecting data in the form of observations and interviews. While the method of data analysis using qualitative and phenomenological methods.The results of this study indicate that the sea alms tradition is a sacred ritual that has become a tradition for traditional fishing communities in Cilacap, by drifting produce in the form of Uborampe or offerings to the sea. And is a manifestation of the symbol of gratitude of fishermen to God, for abundant sea products and requests to avoid the bad things that can happen to fishermen at sea. This ritual is also a symbol of respect for the mystical power that is believed by the fishing community as guardians of the sea and also contains values for life for the fishing community in supporting their activities.